Gamification as a strategy of internal marketing - José Luis Ruizalba Robledo; Fernando Navarro Lucena; Sergio Jiménez Arenas (Intangible Capital, 2013)
Purpose: Theoretical analysis of the phenomenon of gamification and its possible application as a tool for internal marketing, in order to increase job satisfaction and commitment through engagement. Design/methodology/approach: Firstly, review of the literature on gamification and its background within game social reality. Secondly, presentation of several business cases where gamification has been applied. Findings: Focusing the subject of gamification within the field of internal marketing. In addition, a theoretical model of gamification as a tool to improve some consequences on employees’ behavior, such as job satisfaction and commitment through engagement, is proposed,. Various specific hypotheses for future research are proposed based on this model.. Practical implications: Because of the situation of research on internal marketing and gamification, practical implications cannot be deduced in the short term, although they may arise as long as there is empirical evidence of its usefulness. Social implications: Currently there is no empirical evidence to infer social implications. Originality/value: Gamification is a very recent phenomenon that has been scarcely studied.